Modelling the recommendation technique for achieving awareness in serious game for obesity - Muhammad Syafiq Bin Mohd Omar; Marina Ismail; Norizan Mat Diah; Suzana Ahmad; Hayati Abd Rahman (Institute of Advanced Engineering and Science, 2019)
Obesity among children is increasing alarmingly. Therefore it is crucial to instill the awareness about the danger of being obese to the children. To instill the awareness is a challenge. A good approach is required for the message to be accepted and conceptualized by the children. Serious game has been an important mechanism to assist the achievement of many serious purposes other than for entertainment and enjoyment. This paper proposes the implementation of content-based recommendation technique in serious game for obesity awareness among children. Several recommendation techniques for awareness had been studied and the content-based recommendation technique is found to be suitable to be implemented in games. The game was developed according to game development approach and fulfilled the game characteristics. For this preliminary study, 10 children participated in the experiment to determine the effectiveness of the game. The participants were given a pre-and post test to answer before and after playing the game. The result of the test shows that participants achieved the obesity awareness after playing the game. The content-based recommendation technique is applicable to be adopted in serious games to instill awareness in the players.